Poly 3-hydroxybutyrate-co-3-hydroxyhexanoate films can be degraded by the deep-sea microbes at high pressure and low temperature conditions. Issue 2 (3rd April 2019) - Kato, Chiaki; Honma, Aya; Sato, Shunsuke; Okura, Tetsuo; Fukuda, Ryuji; Nogi, Yuichi
ABSTRACT: We have isolated several poly 3-hydroxybutyrate- co -3-hydroxyhexanoate (PHBH) degradable bacteria from the deep-sea sediment samples. The isolated microbes were involved into α-, γ- Proteobacteria group and the phylum Firmicutes, which were commonly diverged in the ocean environment. Four bacterial strains, Bacillus sp. MH10, Alteromonas sp. MH53, Psychrobacillus sp. PL87 and Rheinheimera sp. PL100, were selected as more active strains for the PHBH bio-degradation at high pressure and cold temperature conditions, and showed that those strains were piezotolerant up to 20–30 MPa. Our findings indicated that the PHBH could be well degraded not only in the ocean environment, but also at the deep-sea bottom, by means of those marine microorganisms.